Seasonally Feed-Related Aflatoxins B1 and M1 Spread in Semiarid Industrial Dairy Herd and Its Deteriorating Impacts on Food and Immunity - Saideh Mozafari; Mohammad Mohsenzadeh; Jalil Mehrzad (Journal of Food Quality)
To comparatively determine the levels of aflatoxin (AF) B1 in feedstuffs and of AFM1 in milk from semiarid industrial cattle farms in northeastern Iran during four seasons and to elucidate the effects of mixed AFB1 and AFM1 on bovine granulocytes, 72 feedstuffs (concentrate, silage, and totally mixed ration (TMR)) and 200 bulk milk samples were simultaneously collected for ELISA-based AFs detection. Isolated blood and milk neutrophils (n=8/treatment) were also preincubated with mix of 10 ng/ml AFB1 and 10 ng/ml AFM1 for 12 h; the impact was assessed on neutrophils functions. AFB1 levels in feedstuffs averaged 28 μg/kg (4–127 μg/kg), with TMR maximal (38±6.3 μg/kg), concentrate (32±6.5 μg/kg), and silage (16±1.5 μg/kg). The levels of AFB1 and AFM1 in feedstuffs and milk averaged 42±9.3, 27±2.8, 26±4.1, and 18.5±2.8 μg/kg and 85±7.3, 62±6.1, 46±6.2, and 41±6.5 ppb μg/kg in winter (maximal), autumn, spring, and summer, respectively. Mix of AFB1 and AFM1 weakened various functions of granulocytes. It adds new reason why during winter semiarid raised food-producing animals show more immune-incompetence.